Psychopolitics on Social Media: An Interdisciplinary Analysis of Emotion, Authority, and Online Mobilization - Abdul Robi Padri (Pusat Publikasi Nusantara, 2025)
The intersection of politics, psychology, and digital media has given rise to new forms of power that operate through emotional engagement and algorithmic amplification. Social media platforms have become crucial arenas where authority is constructed, emotions are orchestrated, and collective actions are mobilized. This study investigates the mechanisms of psychopolitics on social media by employing an interdisciplinary approach that integrates political theory, psychology, and digital communication studies. The primary objective is to understand how emotional narratives are strategically deployed to legitimize authority and encourage online mobilization. Using qualitative content analysis and digital ethnography, the research examines selected viral political content on Twitter and Instagram, focusing on the interplay between emotional rhetoric, symbolic authority, and user engagement. The findings reveal that emotional appeals—particularly fear, anger, and hope—are central to digital psychopolitical strategies, often used to polarize public discourse and intensify group identification. Moreover, authority in the digital realm is increasingly derived not only from institutional status but also from emotional resonance and perceived authenticity. These dynamics contribute to a fluid and affective form of governance, where influence is exerted less through direct coercion and more through the modulation of collective feelings. This study highlights the urgent need for critical literacy in navigating emotionally charged political content online.